The Creativity of Conspiracy Theories. (25th March 2021) - Bonetto, Eric; Arciszewski, Thomas
Abstract: Conspiracy theories are narratives, they tell mostly fictional stories. In that sense, conspiracy theories are creative productions similar to other productions involving narratives, such as poems, films, or stories. However, contrary to these productions regularly studied in the field of creativity, conspiracy theories remain unexplored in this field. The present contribution proposes to consider conspiracy narratives as creative products. We discuss the extent to which these narratives meet the criteria of the standard definition of creativity and how their negative individual and societal consequences place conspiracy narratives in the dark side of creativity . We argue that this new perspective on conspiracies may partly change the way we study their construction and their psychological convenience. We finally discuss some theoretical and methodological perspectives linked to this proposition. Overall, this contribution intends to draw the attention of creativity researchers to these real‐world and abundant creative products.